2018
DOI: 10.1061/(asce)st.1943-541x.0002090
|View full text |Cite
|
Sign up to set email alerts
|

Load Transfer and Collapse Resistance of RC Flat Plates under Interior Column Removal Scenario

Abstract: Reinforced concrete (RC) flat-plate structures are vulnerable to punching shear failure at their slab-column connections, potentially leading to a catastrophic progressive collapse. In practice, the slab-column connection above an interior column, removed due to abnormal loads, may be subjected to a concentrated downward force due to the absence of the supporting column and further being pushed due to different live load intensities on individual stories. This force is different to the full design load that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…The tension and compression axial forces and bending moments resisted at the column bases were measured by the load cells throughout T1 and T2. Further details of the design of the custom-made load cells can be found in Xue et al [20].…”
Section: Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations
“…The tension and compression axial forces and bending moments resisted at the column bases were measured by the load cells throughout T1 and T2. Further details of the design of the custom-made load cells can be found in Xue et al [20].…”
Section: Instrumentationmentioning
confidence: 99%
“…Note that T2 was conducted 12 days after T1 due to installation and connection of required experimental instruments, and cutting of column C9. The tests were not repeated as the results were shown to be repeatable in Xue et al [20].…”
Section: Phase 3 -Release Of Jack-bearing Forcementioning
confidence: 99%
See 2 more Smart Citations
“…In real RC frame structures, slabs play an important role in the redistribution of unbalanced loads because slabs are cast in situ together with beams to transfer the unbalanced gravity load induced by an initial local failure. Published experiments on RC slabs under interior, exterior, corner, and penultimate column removal scenarios indicated that a slab will exhibit a two‐dimensional “compressive membrane action” in the primary mechanism stage and a two‐dimensional “tensile membrane action” in the secondary mechanism stage, thereby providing structural resistance. Russell et al conducted dynamic column loss analysis of RC flat slabs and compared with equivalent static cases in order to determine the dynamic amplification factor.…”
Section: Introductionmentioning
confidence: 99%